Art in the Holocaust: On Josef Bor’s Novella Terezínské rekviem and its Reception - Ibler, Reinhard (Poznańskie Studia Slawistyczne, 2017)
The name of the Czech writer Josef Bor (1906–1979) is nearly forgotten today, although he was very successful with two works in the sixties. Both works deal with the Holocaust. The novel Opuštěná panenka (1961) is inspired by the author’s own horrible experiences at Terezín, Auschwitz and other places of the Holocaust. In 1963, the novella Terezínské rekviem followed which is subject of this paper. Bor’s novella is about the Jewish musician Rafael Schächter and his staging of Verdi’s Requiem at Terezín. From the viewpoint of reception, this work is interesting on two counts: on the one hand, in the story the reception and interpretation of art play a crucial role, on the other hand, there are some special features in the reception of the novella itself, as the work has mostly been read in the light of the real events the story is referring to, whereas the text’s literary character has often been neglected.